THE ROLE OF SPEECH IN THE DEVELOPMENT OF MARKETING AND HEALTH MANAGEMENT SCENES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
In today's fast-paced world, the lesson of public speaking plays an important role in the formation of a new worldview among the youth of independent Uzbekistan. Every student who is brought up in the spirit of a new worldview, and every employee who strives for a new worldview needs to know the secrets of correct and literate writing, reading and speaking beautifully, oratory culture, and the art of oratory. all sides must feel it. To man his opinion expression reaches for intuition from the organs one as Allah by language given.